Bioethics of intervention, inter-culturality and non-coloniality - Rivas Muñoz, Fábio (2015)
The proposal of Intervention Bioethics (BI), which arose in the 1990s as a response to the Anglo-Saxon perspective of four universally presumed principles, which though necessary are insufficient in the Latin-American context, has continued its collective construction process. The article shows the common points between this proposal and Latin-American perspectives of inter-cultural and non-colonial issues. Simultaneously, the utilitarian perspective of John Stuart Mill opens the possibilities of approximation between utilitarianism and individual rights, ethically opposing positions for many authors. In addition, we show that BI has consonance with three Unesco declarations on culture, genetic heritage and human rights. All of these elements allow progress towards an epistemological statute of Intervention Bioethics, one of the more important proposals towards a Latin-American vision of this new interdisciplinary territory of knowledge.